Local and landscape environmental heterogeneity drive ant community structure in temperate seminatural upland grasslands. Issue 3 (19th March 2023) - Pérez‐Sánchez, Antonio J.; Schibalski, Anett; Schröder, Boris; Klimek, Sebastian; Dauber, Jens
Abstract: Environmental heterogeneity is an important driver of ecological communities. Here, we assessed the effects of local and landscape spatial environmental heterogeneity on ant community structure in temperate seminatural upland grasslands of Central Germany. We surveyed 33 grassland sites representing a gradient in elevation and landscape composition. Local environmental heterogeneity was measured in terms of variability of temperature and moisture within and between grasslands sites. Grassland management type (pasture vs. meadows) was additionally included as a local environmental heterogeneity measure. The complexity of habitat types in the surroundings of grassland sites was used as a measure of landscape environmental heterogeneity. As descriptors of ant community structure, we considered species composition in terms of nest density, community evenness, and functional response traits. We found that extensively grazed pastures and within‐site heterogeneity in soil moisture at local scale, and a high diversity of land cover types at the landscape scale affected ant species composition by promoting higher nest densities of some species. Ant community evenness was high in wetter grasslands with low within‐site variability in soil moisture and surrounded by a less diverse landscape. Fourth‐corner models revealed that ant community structure response to environmental heterogeneity was mediated mainly by worker size, colony size, and life history traits related with colony reproduction and foundation. We discuss how within‐site local variability in soil moisture and low‐intensity grazing promote ant species densities and highlight the role of habitat temperature and humidity affecting community evenness. We hypothesize that a higher diversity of land cover types in a forest‐dominated landscape buffers less favorable environmental conditions for ant species establishment and dispersal between grasslands. We conclude that spatial environmental heterogeneity at local and landscape scale plays an important role as deterministic force in filtering ant species and, along with neutral processes (e.g., stochastic colonization), in shaping ant community structure in temperate seminatural upland grasslands. Abstract : We followed a multiscale approach to assess the effect spatial environmental heterogeneity on ant community structure seminatural grasslands. Our results showed that soil moisture heterogeneity, extensively grazing management, topographic exposition, and diversity of land cover types shape ant community composition and evenness. Community structure response to environmental heterogeneity was mediated by a small set of morphological, ecological and life history species traits. This study showed that spatial environmental heterogeneity at local and landscape scale plays an important role driving ant community structure in temperate seminatural upland grasslands.